Molecular subtype of ovarian clear cell carcinoma: an analysis of 80 Chinese patients using the TCGA molecular classification of endometrial cancer - Wei Chen; Lu Yan; Qin Li; Shuling Zhou; Ting Hou; Huijuan Yang; Shuang Ye (BMC Cancer, 2025)
Abstract Background To assess the utility of the TCGA molecular classification of endometrial cancer in a well-annotated, moderately sized, consecutive cohort of Chinese patients with ovarian clear cell carcinoma (OCCC). Methods We performed DNA sequencing on 80 OCCC patients via a panel that contains 520 cancer-related genes. The TCGA molecular subtyping method was utilized for classification. The clinicopathological features were analysed, and the survival correlation was assessed for each subtype. Results The most common mutated genes were ARID1A (49%) and PIK3CA (48%). No pathogenic POLE mutations were detected. MSI-high (MSI-H) tumours were observed in 5 (6.3%) patients. A total of 16.3% (13/80) of the patients were classified as the p53 abnormal (p53abn) subtype, and 77.5% (62/80) were classified as the nonspecific molecular profile (NSMP) subtype. All the MSI-H patients had ARID1A mutations, whereas patients with the p53abn subtype had the lowest percentage of ARID1A mutations (27.3%). No significant differences were observed between the molecular subtypes and clinicopathological features. The progression-free survival and overall survival of the entire cohort were closely associated with FIGO stage (p < 0.01), the presence of residual tumour (p < 0.01), and the platinum response (p < 0.01). Molecular classification did not significantly impact prognosis. Univariate analysis revealed that TP53 mutations in advanced-stage (FIGO III-IV) patients were associated with shorter survival. Conclusions We did not find prognostic significance of TCGA molecular subtyping in OCCC. POLEmuts are extremely rare, and the incidence of MSI-H and p53abn tumours is also quite low. Further subtyping of the NSMP subgroup is warranted.